Screening and Isolation of Cellulolytic Bacteria From Bagasse and Characterization of The Cellullase Produced - Hartanti, Lanny; Susanto, Fandy; Utami, Caesilia Putri; Sukarti, Emi; Setiawan, Henry Kurnia; Ervina, Martha (UNEJ e-Proceeding, 2014)
The research of screening and isolation of cellulase-producing bacteria from bagasse had been done. The objectives of the research were to obtain cellulolytic bacteria isolate, to determine the genus of the isolates and also to characterize the crude enzymes produced. One isolate with the highest activity was chosen to be purified further bystreak plate and pour plate methods in carboxyl methyl cellulose(CMC)  agar media. The genus of the pure isolated bacteria was further characterized by macroscopic and microscopic properties, and biochemical assays using conventional methods and MicrobactTM Kit: gram-negative identification system (Oxoid). The result showed that the isolated cellulolytic bacteria had a close character similarity to Bacillus pumilus. The isolate was grown on MHB + CMC media with 2 hours of adaptation phase followed by logarithmic phase until 21 hours of incubation. Cellulase was started to be produced after 4 hours of fermentation and reached the highest activity at 21 hours of fermentation. The cellulase produced had the pH optimum at pH 5 and a temperature optimum at 60 °C, with optimum activity ranging from 0.0231 to 0.0264 U /ml. One unit of cellulase activity is defined as the amount of enzyme that will catalyze the production of 1 mg of glucose per minute at 37°C and pH 7.0. Keywords:  bagasse, bacteria isolation, cellulolytic, biochemical characterization, enzyme characterization